2017
DOI: 10.1039/c7cy00060j
|View full text |Cite
|
Sign up to set email alerts
|

Switching a nitrilase from Syechocystis sp. PCC6803 to a nitrile hydratase by rationally regulating reaction pathways

Abstract: Based on this mechanism, a nitrilase was engineered to shift the reaction pathway from formation of acid to formation of amide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…Variation in amide 5 a formation was studied by MD sampling of the wt Ss NIT and three mutants. The results showed that NH 2 group in the tetrahedral intermediate for the mutant was more easily protonated and resulted in less amide 5 a formation, being consistent with the studies by Jiang et al [24] . (Supporting Information, Table S10).…”
Section: Resultssupporting
confidence: 90%
“…Variation in amide 5 a formation was studied by MD sampling of the wt Ss NIT and three mutants. The results showed that NH 2 group in the tetrahedral intermediate for the mutant was more easily protonated and resulted in less amide 5 a formation, being consistent with the studies by Jiang et al [24] . (Supporting Information, Table S10).…”
Section: Resultssupporting
confidence: 90%
“…QueF and nitrilase appear to utilize a highly similar mechanism to promote the covalent thioimidate intermediate (Scheme 1A). 9,14,41 In the nitrilase, a triad of cysteine/ glutamic acid/lysine constitutes the active-site apparatus. 8,16,41 Like Asp197 in QueF, the glutamic acid is central for catalytic nucleophile activation and for acid-base catalysis.…”
Section: View Article Onlinementioning
confidence: 99%
“…[1][2][3] They also have significant applications in synthetic chemistry wherein nitriles often represent important intermediates. 4,5 The nitrile group is converted by hydrolytic enzymes to an amide or to a carboxylic acid [6][7][8][9] and by reductive enzymes to an amine. [10][11][12][13] Despite the different reactivities, nitrile-converting enzymes share covalent catalysis from an active-site nucleophile as a common feature of their mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations